Definitive radiotherapy for squamous cell carcinoma of the oral cavity: a single-institution experience - Uzun-Lang, Kristin; Baur, Melissa; Held, Thomas; El-Shafie, Rami; Moratin, Julius; Freudlsperger, Christian; Plath, Karim; Bougatf, Nina; Hoffmann, Jürgen; Plinkert, Peter K.; Debus, Jürgen; Adeberg, Sebastian (Radiology and oncology, 2021)
Background - Surgery is standard of care for oral cavity cancer (OCC). We provide a single-institution experience using definitive radiotherapy (RT) with or without concurrent systemic therapy for primary unresectable OCC. - - Patients and methods - We retrospectively examined 49 patients with non-metastatic primary unresectable OCC treated with definitive RT between 2000 and 2019. The majority of patients (63.3%) were treated with definitive chemoradiotherapy while 26.5% were given single-agent cetuximab weekly simultaneous to definitive RT. Five patients were treated with definitive RT alone because of limited disease and no nodal involvement. - - Results - Median follow-up was 73 months (range, 6-236 months), median progression free survival (PFS) was 42 months (range, 2-157 months), median local disease-free survival (LDFS) was 44 months (range, 2-157 months) and median overall survival (OS) from the time of RT initiation was 52 months (range, 5-236 months). There were 65.3% locoregional failures, 84.4% local and 15.6% distant metastasis. The majority of patients with local failure presented with American Joint Committee on Cancer (AJCC) Stage III-IV disease (59.2%). The 5-year Kaplan-Meier estimates for OS (III-IV vs. I-II) was 22.8% vs. 54.2 % (p = 0.03, HR 2.090, 1.1-4.2). Patients who were treated with systemic therapy had a significant better 5-year overall survival compared to those with RT
Gesehen am 20.12.2021